Effects of rTMS conditioning over the fronto-parietal network on motor versus visual attention. - Rounis, E; Yarrow, K; Rothwell, J (2007)
Many studies have shown that visuospatial orienting attention depends on a network of frontal and parietal areas in the right hemisphere. Rushworth et al. [Rushworth, M. F., Krams, M., and Passingham, R. E. The attentional role of the left parietal cortex: The distinct lateralization and localization of motor attention in the human brain. Journal of Cognitive Neuroscience, 13, 698-710, 2001] have recently provided evidence for a left-lateralized network of parietal areas involved in motor attention. Using two variants of a cued reaction time (RT) task, we set out to investigate whether high-frequency repetitive transcranial magnetic stimulation (rTMS; 5 Hz) delivered "off-line" in a virtual lesion paradigm over the right or left dorsolateral prefrontal cortex (DLPFC) or the posterior parietal cortex (PPC) would affect performance in a motor versus a visual attention task. Although rTMS over the DLPFC on either side did not affect RT performance on a spatial orienting task, it did lead to an increase in the RTs of invalidly cued trials in a motor attention task when delivered to the left DLPFC. The opposite effect was found when rTMS was delivered to the PPC: In this case, conditioning the right PPC led to increased RTs in invalidly cued trials located in the left hemispace, in the spatial orienting task. rTMS over the PPC on either side did not affect performance in the motor attention task. This double dissociation was evident in the first 10 min after rTMS conditioning. These results enhance our understanding of the networks associated with attention. They provide evidence of a role for the left DLPFC in the mechanisms of motor preparation, and confirm Mesulam's original proposal for a right PPC dominance in spatial attention [Mesulam, M. M. A cortical network for directed attention and unilateral neglect. Annals of Neurology, 10, 309-325, 1981].